Multi-mode/multi-band RF transceivers for wireless communications : advanced techniques, architectures, and trends - Staszewski, Robert Bogdan, 1965-; Hueber, Gernot, 1972-; John Wiley & Sons; IEEE Xplore (Online service) ([Hoboken, New Jersey] : Wiley, 2011)
State-of-the-art and beyond technologies to be used in future multi-mode wireless communication systemsCurrent and future mobile terminals become increasingly complex because they have to deal with a variety of frequency bands and communication standards. Achieving multiband/multimode functionality (3G and beyond) is especially challenging for the RF-transceiver section.This volume presents cutting-edge physical layer technologies for multi-mode wireless RF transceivers, specifically RF, analog, and mixed-signal and digital circuits and architectures. Providing the most comprehensive treatment of this topic available, it features original contributions from distinguished researchers and professionals from both academia and industry, who anticipate the major trends and needs of future wireless system developments.Divided into four sections, Multi-Mode/Multi-Band RF Transceivers for Wireless Communications covers:. Transceiver concepts and design: software-defined radio front-ends/transceivers, adaptive multi-mode RF front-end circuits, delay alignment between amplitude and phase paths in a digital polar transmitter, and front-end RF passive integration, as well as versatile data converters. Receiver design: OFDM transform-domain receivers for multi-standards, discrete-time processing of RF signals, oversampled ADC using VCO-based quantizers, RF receiver front-ends for mobile terminals, and digitally enhanced alternate path linearization of RF receivers. Transmitter techniques: Linearity and efficiency strategies, CMOS RF power amplifiers for mobiles, and digitally assisted RF architectures. Digital Signal Processing for RF transceivers: RF impairment compensation for future radio systems, techniques for the analysis of digital bang-bang PLLs, and low-power spectrum processors for cognitive radiosThe remarkable insight into the essential transceiver building blocks to be used in future multi-mode wireless communication systems makes this an invaluable resource for engineers and researchers from academia and industry working on circuits and architectures of wireless transceivers, as well as for RF design engineers in semiconductor companies and graduate students taking advanced courses on wireless communication circuits.
17.2 Paradigm Shift from SDR to CR -- 17.3 Challenge and Trends in RFIC/System -- 17.4 Analog Signal Processing -- 17.5 Spectrum Sensing -- 17.6 Multi-Resolution Spectrum Sensing -- 17.7 MRSS Performance -- 17.8 Conclusions -- References -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Wireless LANs -- Equipment and supplies -- Design and construction; Cell phones -- Design and construction; Wireless communication systems -- Equipment and supplies -- Design and construction; Radio -- Transmitter-receivers.; Electronic books